Adaptation to Climate Change, Conservation and Financial Feasibility in Heritage Buildings: A Nexus of Ideological Divergence in Post-Flood Disaster Reconstruction - Amadi Alolote Ibim (PT. ELSHAD TECHNOLOGY INDONESIA, 2024)
Reconstruction following climate change induced disasters is often required after possible destruction of the built heritage. Achieving greater disaster resilience and reducing disaster risk due to climate change requires that such reconstruction must be balanced with financial and technical feasibility while conserving the historic character of the heritage building. The ‘Build-Back-Better’ mantra is mostly embraced during disaster induced reconstruction, and seeks to build safer and more resilient structures, to reduce pre-disaster vulnerabilities. The ‘Build-Back-Better’ approach assumes that there were vulnerabilities within the pre-disaster built environments that need to be rectified during reconstruction to enhance resilience. As such, achieving building conservation and climate adaptation during reconstruction might at first glance appear completely divergent. Conservation mostly focuses on maintaining the fabric of a place in its existing state, while adaptation may require updating/altering the components of an existing building. However, a more thorough understanding may lead to the conclusion that there is a convergence. This is because the conservation of the built heritage should contribute to resilience, in many ways similar to adaptation, especially in the context of post-disaster recovery. A divergence will result in a fairly unprecedented exposure to natural hazards triggered by climate change, and amplify the performance deficiencies, in terms of functional, technological and normative obsolescence. A convergence is needed due to the increasing requirements of safety, well-being and accessibility of the historic and architectural values, whose conservation is sought. Flooding is the most widely spread climate change induced disaster that affects the built environment globally. This study highlights how heritage conservation can techno-economically align with the resilience agenda, during reconstruction following flood disasters induced by climate change.